Respuesta :
Answer:
x = 3 +√23 and x = 3 - √23
Step-by-step explanation:
The given equation 3x^2 -18x +5 = 47
This can be written as 3x^2 -18x + 5 - 47 =0
3x^2 -18x - 42 = 0
Here we have to use the quadratic formula.
x = [tex]\frac{-b +/- \sqrt{b^2 - 4ac} }{2a}[/tex]
From the given equation, a = 3, b = -18 and c = -42
Plug in these values in the above formula, we get
x = [tex]\frac{-(-18) +/- \sqrt{(-18)^2 - 4.3.(-42)} }{2.3}[/tex]
x = [tex]\frac{18 +/- \sqrt{828} }{6}[/tex]
Simplifying the above expression, we get
x = 3 +√23 and x = 3 - √23
Hope this will helpful.
Thank you.